Growth and pigment constituents of the red alga Gracilaria edulis (Gmelin) Silva, grown at different depths - Jayasankar, Reeta; Varghese, Sally (Indian Journal of Fisheries, 2011)
Chlorophyll-a, phycoerythrin, phycocyanin and allophycocyanin of the red alga, Gracilaria edulis, cultured in outdoor tanks under natural light at different depths were estimated. Crop growth rate and pigment contents in relation to varjdng light intensities (depth) were observed. An inverse relationship between pigment content and the light intensity was noted. But growth rate was more at higher light intensities.